Visible light spectroscopic analysis of Methylene Blue in water; the resonance virtual equilibrium hypothesis. (February 2019) - Fernández-Pérez, Amparo; Valdés-Solís, Teresa; Marbán, Gregorio
Abstract: After a critical approach to the centennial literature on Methylene Blue self-aggregation in water, accurate visible-light absorption spectra and thermodynamic equilibrium constants for the monomeric and dimeric forms of this dye in water at different temperatures were obtained by means of a novel procedure based on the Beer-Lambert equation. A thermo-solvatochromic effect was clearly detected in the monomer spectra, which we believe to be the main source of inaccuracy in all previous works. The only published explanation for this phenomenon, the existence of a colorless form of the monomer, is refuted here. Instead, a new notion has been introduced; the resonance virtual equilibrium hypothesis. According to this hypothesis the temperature-dependent absorption behavior of the monomer is provoked by the change in its electron charge distribution with the variation in the temperature-dependent dielectric constant of water. The monomer charge distribution stands between those of the virtual resonance forms, being the absorption spectrum of the monomer a composition of the theoretical spectra for the virtual mesomers, whose proportion is established by a temperature-dependent equilibrium constant. The application of this hypothesis allowed the virtual equilibrium constants and spectra for the mesomers to be evaluated with remarkable accuracy. Graphical abstract: Highlights: First accurate thermodynamic parameters for MB monomer self-aggregation in water. Resonance virtual equilibrium hypothesis to understand MB monomer thermo-solvatochromism. Flawless Visible light absorption spectra for MB monomeric resonance forms and MB dimer.